Oeuvres. Jacob de la junta, he of the laws - Perona, José (GLOSSAE. European Journal of Legal History, 1988)
The edition of the first of the works of Jacob of the Laws that Professor Roudil presents in this volume gathers and culminates the extensive work and knowledge of one of the most illustrious connoisseurs of the medieval language -especially the foral language- of the Iberian Peninsula.